Studying the Use of Public Spaces in the Library - May, Francine (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Methods for studying the public places of libraries, including mental mapping, observation and patron mapping are reviewed. Reflections on the experience of adapting an observational technique for use in multiple different library spaces are shared. Sont passées en revue les méthodes pour étudier la place publique des bibliothèques, y compris les représentations mentales, l’observation et la catégorisation des usagers. L’auteure partage ses réflexions sur l’expérience d’adapter une technique d’observation à différents espaces de bibliothèque. ***Full paper in the Canadian Journal of Information and Library Science***